Kajian Yuridis Legalisasi Aborsi Bagi Korban Tindak Pidana Pemerkosaan dalam Perspektif Hukum Positif - Evi Yanti (Universitas Islam Indonesia, 2020)
Conflicts regarding the legalization of abortion occur because of the gap between one legislation and another. The problems in this study are: first, how to legalize abortion for victims of rape in the perspective of positive law; Second, as well as the legal protection for doctors and patients who perform such abortions. Women who get pregnant for becoming rape victims choose abortion as a way to end their pregnancy are deemed as perpetrators of the crime of abortion In the criminal law literature The research method used is a normative juridical method with an approach to legislation and comparative studies. The results of this study are first, abortion is a prohibited act, but if it is in an emergency situation and the victim is raped, abortion can be undertaken; second, legal protection for victims includes; a. The provision of medical and psychosocial assistance services to rape victims who have abortions in accordance with applicable laws and regulations as described in Article 6 of Law no. 13 of 2006 on the Protection of Witnesses and Victims; b. The compensation provided by the perpetrator is in accordance with the provisions of Article 7 paragraph (1) letter b of Law No. 13 of 2006 on the Protection of Witnesses and Victims; c. Restitution, compensation given by the state because the perpetrator is unable. it is possible as an effort to provide services to victims of crime in the context of developing welfare and justice in accordance with the provisions of Article 7 paragraph (2) of Law No.r 13 of 2006 on the Protection of Witnesses and Victims